Evaluation of the mechanisms of damage to flexible ureteroscopes and suggestions for ureteroscope preservation. - Sooriakumaran, P; Kaba, R; Andrews, H; Buchholz, N (2005)
AIM: To investigate the causes and costs of flexible ureteroscope damage, and to develop recommendations to limit damage. METHODS: The authors analysed repair figures and possible causes of damage to 35 instruments sent for repair to a leading UK supplier over a 1-year period, and calculated cost figures for maintenance of the instruments as opposed to repair and replacement costs. RESULTS: All damages were handling-induced and therefore did not fall under the manufacturer's warranty: 28 % were damaged by misfiring of the laser inside the instrument; 72 %, mainly crushing and stripping of the ureteroscope shaft tube, were likely to have occurred during out-of-surgery handling, washing and disinfection. Seventeen (4 %) instruments were not repaired and consequently taken out of service due to the extensive costs involved. Eighteen (51 %) ureteroscopes were repaired at an average cost of 10 833 USD. CONCLUSION: Damages to flexible ureteroscopes bear considerable costs. Most damages occur during handling between surgical procedures. Thorough adherence to handling procedures, and courses for theater staff and surgeons on handling flexible instruments may help to reduce these damages and prove a cost-saving investment. The authors provide a list of recommended procedural measures that may help to prevent such damages.